Identification of cDNA clones coding for rat tyrosine hydroxylase antigen. - Lamouroux, A (1982)
Five recombinant DNA plasmids have been constructed that contain structural gene sequences for rat tyrosine hydroxylase [TyrOHase; tyrosine 3-monooxygenase; L-tyrosine, tetrahydropteridine:oxygen oxidoreductase (3-hydroxylating), EC 1.14.16.2]. Rat pheochromocytoma PC 12 cell line, which contains relatively high levels of catecholamine-synthesizing enzymes, was used to purify RNA. TyrOHase cDNA clones were identified by screening 350 cDNA clones constructed from partially purified TyrOHase mRNA. A rapid and powerful screening of the recombinant clones by differential colony hybridization was possible because TyrOHase is a tissue-specific protein. The final selection relied on the ability of cDNA inserts to hybridize specifically to TyrOHase mRNA as judged by cell-free translation and immunoprecipitation. Blot hybridization analysis of polyadenylylated RNA from PC 12 cells indicated a major mRNA species of 1.9 kilobases. A species of the same size was identified from a human pheochromocytoma tumor, indicating a crossreactivity between rat TyrOHase cDNA and human TyrOHase mRNA.